NORMATIVE INDICATORS OF DENTAL MANUFACTURING STEPS DURATION OF SCROLLABLE BRIDGES BASED ON PLASTIC BURNOUT ABUTMENTS AND ABUTMENTS WITH PLATFORM FOR BONDING RELYING ON IMPLANTS - E.V. Diiev; V.A. Labunets; T.V. Diieva (Український стоматологічний альманах)
Dental implant technology that is widely used in medical practice in Ukraine, does not have full legal status to the application, also due to the lack of standard indicators and duration of clinical dental specialists execution phases of its corresponding profile.